Peningkatan Produksi dan Kualitas Produk Unggulan Kerupuk Ikan Desa Pangkahkulon Kecamatan Ujung Pangkah-Gresik Jawa Timur - Mochamad Arif Zainul Fuad; Feni Iranawati; Hartati Kartikaningsih; Kristin Rosalina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Pangkahkulon Village is a coastal village in Ujung Pangkah District, Gresik with more than 70% of its area being fish and shrimp farming ponds. To improve the household economy, many fishermen set up home industries (IRT) in processing fishery products. Based on the results of the Pappingkulon Village Potential Mapping, the number of fishery product businesses reached 98 units. The majority of these household businesses are the fish cracker industry with a total of 67 units. The first year of the Mitra Desa Development Program (PPDM) aims to empower communities through the development and improvement of the production and competitiveness of superior village products. Therefore, based on the mapped potential and discussion with Pangkahkulon Village officials, it was decided that the superior product of Pangkahkulon Village to be appointed was fish crackers. In general, the activities carried out in the first year were to increase production and competitiveness of IRT fish crackers, one of which was through the help of production equipment. The production facilities which were donated to IRT were in the form of two units of the mixer and one unit of automatic cracker dough cutter. This tool was granted to answer the main problem experienced by IRT, which is the inconsistency of cracker dough results because so far the making of the dough is still done by hand. Tool assistance through the PPDM program is able to increase production capacity by up to 35%.